Preaching in the Face of Poverty (Homiletic, 2016)
The purpose of this paper is to reflect on Luke 16:19-24, using that text as the starting point for a discussion about preaching in the African American church’s context. It also examines how African American preaching can and should speak to the growing issue of poverty and income inequality in the United States in general, but more precisely within the African American community in particular. Ultimately, this paper suggests some specific ways that sermons can challenge both adherents to the Christian faith and leaders in various arenas of civil society to respond to this growing problem of poverty and income inequality.